Phenomenological Analysis of the Implementation of Integrated Islamic Curriculum in Al-Mawaddah Integrated Islamic Elementary School Ponorogo - Meyrlin Kusumaningrum; Khuriyah (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to analyze the implementation of the integrated Islamic curriculum at the Al-Mawaddah Ponorogo Integrated Islamic Elementary School (SDIT) using a phenomenological approach. This research focuses on the life experiences and perceptions of education actors in integrating Islamic values into the national curriculum. Qualitative research methods with a phenomenological approach are used with data collection techniques through in-depth interviews, participatory observations, and documentation studies. Informants include the principal, teachers, students, and parents of students. The results of the research indicate that the implementation of the integrated Islamic curriculum at SDIT Al-Mawaddah Ponorogo is carried out through three main dimensions: (1) integration of Islamic values in each subject, (2) application of a student-centered learning approach with an emphasis on project-based learning and problem solving, and (3) development of a holistic evaluation system that includes cognitive, affective, and psychomotor aspects. The challenges faced are the lack of integrated teaching materials, and the complexity of the evaluation system. This research concludes that the success of the implementation of the integrated Islamic curriculum is highly dependent on the commitment of all school parties and the support of a conducive educational environment.